Efeitos da ghrelina, GHRP-6 e GHRH sobre a secreção de GH, ACTH e cortisol em pacientes com diabetes mellitus tipo 1 - Sa, Larissa Bianca Paiva Cunha de [UNIFESP] (2009)
In type 1 diabetes mellitus (T1DM), GH responses to provocative stimuli are normal or exaggerated while the hypothalamic-pituitary-adrenal axis has been less studied. Ghrelin is a GH-secretagogue which also increases ACTH and cortisol levels, similarly to GHRP-6. Ghrelin Ls effects in patients with T1DM have not been evaluated. We, therefore, studied GH, ACTH and cortisol responses to ghrelin and GHRP-6 in 9 patients with T1D1 (HbA1c: 11.7 }1.3%; mean }SE) and 9 control subjects. GHRH- induced GH release was also evaluated. Mean basal GH levels (Rg/L) were higher in T1DM (3.5 }1.2) than in controls (0.6 }0.3). Analyzing ƒ¢AUC GH values (Rg/L.120min), no significant differences were observed in T1DM (ghrelin: 3148 }427; GHRP-6: 1428 }299; GHRH: 885 }184) compared to controls (ghrelin: 3228 }1036; GHRP-6: 1271 }217; GHRH: 643 }178). In both groups, ghrelin-induced GH release was higher than after GHRP-6 and GHRH. There was a trend (p=0.055) to higher mean basal cortisol values (Rg/dL) in T1DM (11.7 }1.5) compared to controls (8.2 }0.8). No significant differences were seen in ƒ¢AUC cortisol values (Rg/dL.90min) in both groups after ghrelin (DM1:303 }106; controls: 467 }86) and GHRP-6 (DM1:135 }112; controls: 187 }73). Mean basal ACTH values (pg/mL) were similar in T1DM (19.9 }3.4) and controls (14.5 }2.3). No differences were seen in ƒ¢AUC ACTH levels (pg/mL.90min) in both groups after ghrelin (DM1:1372 }771; controls: 1394 }327) and GHRP-6 (DM1: 257 }291; controls: 423 }211). In summary, patients with T1DM have normal GH responsiveness to ghrelin, GHRP-6 and GHRH. ACTH and cortisol release after ghrelin and GHRP-6 is also similar to controls. Our results suggest that chronic hyperglycemia of T1DM does not interfere with GH, ACTH and cortisol releasing mechanisms stimulated by these peptides.